2014
DOI: 10.1038/bjc.2014.367
|View full text |Cite
|
Sign up to set email alerts
|

Tumour microenvironment of both early- and late-stage colorectal cancer is equally immunosuppressive

Abstract: BackgroundTumour microenvironment (TME) of advanced colorectal cancer (CRC) suppresses dendritic cell (DC) maturation. Here, our aim was to determine how the microenvironment of early-stage tumours influences DCs.Methods:Tumour-conditioned media (TCM) was generated by culturing explant tumour tissue in vitro (n=50). Monocyte-derived DCs (MDDCs) of healthy donors or cancer patients were pretreated with TCM and stimulated with lipopolysaccharide (LPS). DC maturation was assessed by flow cytometry and cytokine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 25 publications
0
28
0
2
Order By: Relevance
“…The CRC microenvironment contains immunosuppressive cytokines such as TGF-β and IL-10, which limit antitumor T cell responses (136). For prognosis, a high density of CD8 + T cells in the primary lesion is associated with less tumor invasion and improved survival, whereas a high density of Tregs is associated with poorer outcomes (137).…”
Section: Immune Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The CRC microenvironment contains immunosuppressive cytokines such as TGF-β and IL-10, which limit antitumor T cell responses (136). For prognosis, a high density of CD8 + T cells in the primary lesion is associated with less tumor invasion and improved survival, whereas a high density of Tregs is associated with poorer outcomes (137).…”
Section: Immune Microenvironmentmentioning
confidence: 99%
“…Tumor-infiltrating Tregs play an important role in preventing an antitumor T cell response, and a unique latency-associated peptide (LAP) + Treg was recently discovered in CRC tumors that secretes more IL-10 and TGF-β and is more immunosuppressive than LAP − Foxp3 + Tregs (138). Dendritic cells, key players in orchestrating an immune response, are also suppressed in CRC (136). Tumor-derived IL-6, stimulated in part by leptin, promotes accumulation of myeloid-derived suppressor cells (MDSCs) (139) and upregulates dendritic cell expression of arginase (136), both processes that attenuate CD4 + and CD8 + T cell responses.…”
Section: Immune Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor microenvironment (TME) represents a new hallmark of cancer [3] and includes complex cooperation between tumor cells with stroma, immune cells, and endothelial cells. Moreover, the presence of inflammatory cells and inflammatory mediators such as chemokines and cytokines related to TME facilitate tumor progression, including CRC [4]. Sometimes, a single cytokine (e.g., growth factor) can activate signals of complex molecular cascades resulting in tumor progression and development.…”
Section: Introductionmentioning
confidence: 99%
“…[44] The study was terminated due to the occurrence of the side effects and the lack of efficacy in disease progression. [46][47][48] www.advancedsciencenews.com www.advtherap.com Structurally related to NAMI-A are KP1019 [49,50] and its watersoluble formulation (N)KP1339 (Figure 1), and both underwent phase I clinical investigations in patients with solid tumors. [22] Cytotoxicity studies of NAMI-A and other experimental ruthenium-based drugs showed that simple in vitro (monolayer or co-culture) results are a poor indicator of in vivo activity.…”
Section: Overview Of Clinically Evaluated Ruthenium-based Compoundsmentioning
confidence: 99%